Mutation in Protein Disulfide Isomerase a3 Causes Neurodevelopmental Defects by Disturbing Endoplasmic Reticulum Proteostasis - Morales-Munoz, B; Rozas-Salas, C; Contreras-Pacheco, D; Piña-Muñoz, R (John Wiley and Sons Inc, 2022)
Recessive gene mutations underlie many developmental disorders and often lead to disabling neurological problems. Here, we report identification of a homozygous c.170G>A (p.Cys57Tyr or C57Y) mutation in the gene coding for protein disulfide isomerase A3 (PDIA3, also known as ERp57), an enzyme that catalyzes formation of disulfide bonds in the endoplasmic reticulum, to be associated with syndromic intellectual disability. Experiments in zebrafish embryos show that PDIA3C57Y expression is pathogenic and causes developmental defects such as axonal disorganization as well as skeletal abnormalities. Expression of PDIA3C57Y in the mouse hippocampus results in impaired synaptic plasticity and memory consolidation. Proteomic and functional analyses reveal that PDIA3C57Y expression leads to dysregulation of cell adhesion and actin cytoskeleton dynamics, associated with altered integrin biogenesis and reduced neuritogenesis. Biochemical studies show that PDIA3C57Y has decreased catalytic activity and forms disulfide-crosslinked aggregates that abnormally interact with chaperones in the endoplasmic reticulum. Thus, rare disease gene variant can provide insight into how perturbations of neuronal proteostasis can affect the function of the nervous system. © 2021 MRC Laboratory of Molecular Biology. Published under the terms of the CC BY 4.0 license.